SARS-CoV-2 infection among healthcare workers: the role of occupational and household exposures during the first three pandemic waves in Quebec, Canada - Sara Carazo; Geoffroy Denis; Lauriane Padet; Pierre Deshaies; Jasmin Villeneuve; Bianka Paquet-Bolduc; Denis Laliberté; Denis Talbot; Gaston De Serres (Cambridge University Press, 2023)
Abstract Objective: We described the evolution of SARS-CoV-2 source of infection in a cohort of healthcare workers (HCWs) of Quebec, Canada, during the first three pandemic waves. We also estimated their household secondary attack rate (SAR) and its risk factors. Design: Cross-sectional surveys. Participants: HCWs with a SARS-CoV-2 infection confirmed by polymerasa chain reaction and diagnosed between March 2020 and May 2021. Methods: We collected demographic, clinical, vaccination, and employment information, self-reported perceived source of infection, and transmission to household members during the first three pandemic waves. SAR was calculated for households with ≥2 members where the HCW was the index case. A Poisson regression model estimated the association between risk factors and SAR. Results: Among the 11,670 HCWs completing the survey, 91%, perceived their workplace as the source of infection during the first wave (March-July 2020), 71% during the second wave (July 2020-March 2021), and 40% during the third wave (March-May 2021). Conversely, HCWs reported an increasing proportion of household-acquired infections with each wave from 4% to 14% and 33%, respectively. The overall household SAR of 7,990 HCWs living with ≥1 person was 30% (95%CI: 29-30). SAR increased with the presence of symptoms, older age, and during Alpha-variant predominant period. Conclusions: HCWs and their household members were largely affected during the first pandemic waves of COVID-19, but the relative importance of occupational exposure changed overtime. Pandemic preparedness in healthcare settings is essential to protect HCWs from emerging biological hazard exposures.